Semi‐quantitative risk assessment by expert elicitation of potential introduction routes of African swine fever from wild reservoir to domestic pig industry and subsequent spread during the Belgian outbreak (2018–2019). Issue 5 (23rd March 2021) - Mauroy, Axel; Depoorter, Pieter; Saegerman, Claude; Cay, Brigitte; De Regge, Nick; Filippitzi, Maria‐Eleni; Fischer, Claude; Laitat, Martine; Maes, Dominiek; Morelle, Kevin; Nauwynck, Hans; Simons, Xavier; et al.
Abstract: Since the introduction in Georgia in 2007 of an African swine fever (ASF) genotype 2 virus strain, the virus has rapidly spread to both Western European and Asian countries. It now constitutes a major threat for the global swine industry. The ongoing European transmission cycle has been related to the 'wild boar habitat' with closed transmission events between wild boar populations and incidental spillovers to commercial and non‐commercial (backyard) pig holdings. During the epidemic in Belgium, only wild boar were infected and although the introduction route has not yet been elucidated, the 'human factor' is highly suspected. While ASF was successfully contained in a small region in the Southern part of Belgium without affecting domestic pigs, the risk of spillover at the wild/domestic interface remains poorly assessed. In this study, we used a semi‐quantitative method, involving national and international experts, to assess the risk associated with different transmission routes for ASF introduction from wild boar to domestic pig holdings and subsequent dissemination between holdings in the Belgian epidemiological context. Qualitative responses obtained by our questionnaire were numerically transformed and statistically processed to provide a semi‐quantitative assessment of the occurrence of the hazard and a ranking of all transmission routes. 'Farmer', 'bedding material', 'veterinarian' and 'professionals from the pig sector' were considered as the most important transmission routes for ASF introduction from the wild reservoir to pig holdings. 'Animal movements', 'farmer', 'veterinarian', 'iatrogenic', 'animal transport truck' and 'animal care equipment' were considered as the most important transmission routes posing a risk of ASF spread between pig holdings. Combined with specific biosecurity checks in the holdings, this assessment helps in prioritizing risk mitigation measures against ASF introduction and further spread in the domestic pig industry, particularly while the ASF situation in Western Europe is worsening.